Development of thresholds for insecticidal control of New Zealand flower thrips on nectarines in spring - McLaren, G.F.; Fraser, J.A. (New Zealand Plant Protection, 2000)
Numbers of adult and larval New Zealand flower thrips Thrips obscuratus were recorded daily on nectarines from flowering (early September) to shuck fall (early November) over 5 years Adults were more common than larvae and occurred throughout this period increasing to their highest numbers in late October Larvae occurred for three weeks from petal fall Adults were released weekly onto bagged nectarine flowers or fruitlets from flowering to shuck fall Damage to the fruit was assessed in November Adults caused the most severe damage when released during flowering; slightly less damage was caused after petal fall and minor damage occurred in the weeks before shuck fall Adult feeding did not affect fruit set Three thresholds based on adult numbers are proposed for determining the need for insecticidal control in an Integrated Fruit Production programme for nectarines These thresholds reflect the decreasing risk of damage through the sensitive period